TANTANGAN DAN PELUANG AKUNTAN PUBLIK DI ERA DIGITALISASI - Rasyid, Ghofur; Haliah; Nirwana (Business, Accounting and Management Journal, 2024)
The digital transformation of public accounting is driving change in the delivery of government services, involving the use of technologies such as data analysis, artificial intelligence and process automation to optimize public services. This research uses a descriptive approach; The discussion comes from relevant literature research, including several books, scientific articles and journals. The aim of this research is to provide a comprehensive overview of digital change in public accounting, as well as the opportunities and obstacle associated with the adoption of this technology. Ease of connection and accessibility through e-government, open government, and greater use of data are opportunities. In addition, it talks about limitations in the use and management of digital technology, including data security. The digital revolution of public administration has had a significant impact on government operations and public services. A number of fields, such as politics, government, health, education and economics, have become more accessible thanks to digital technology. Everyone is encouraged to be transparent, effective, involved and use data for decision making. Additionally, digital transformation enables opportunities for open, transparent and capable government.